2001
DOI: 10.1139/cjfas-58-8-1603
|View full text |Cite
|
Sign up to set email alerts
|

Primary determinants of macrophyte community structure in 62 marshes across the Great Lakes basin: latitude, land use, and water quality effects

Abstract: We collected water quality, land use, and aquatic macrophyte information from 62 coastal and inland wetlands in the Great Lakes basin and found that species richness and community structure of macrophytes were a function of geographic location and water quality. For inland wetlands, the primary source of water quality degradation was inputs of nutrients and sediment associated with altered land use, whereas for coastal wetlands, water quality was also influenced by exposure and mixing with the respective Great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 32 publications
9
72
1
Order By: Relevance
“…A number of studies have found these to be the most significant factors governing the abundance, composition and distribution of macrophytes (Bini et al 1999;Lougheed et al 2001;Pandit 2002). It is well documented that the underwater light plays an important role in determining the depth distribution of different groups of aquatic macrophytes (Sculthorpe 1971;Chambers and Kalff 1985;Dale 1986;Chambers and Prepas 1988;Hrivnak et al 2006).…”
Section: Lightmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have found these to be the most significant factors governing the abundance, composition and distribution of macrophytes (Bini et al 1999;Lougheed et al 2001;Pandit 2002). It is well documented that the underwater light plays an important role in determining the depth distribution of different groups of aquatic macrophytes (Sculthorpe 1971;Chambers and Kalff 1985;Dale 1986;Chambers and Prepas 1988;Hrivnak et al 2006).…”
Section: Lightmentioning
confidence: 99%
“…A lot of research has been done from time to time to evaluate the effects of water quality, sediment characteristics and geological formations on aquatic macrophyte distribution (Kaul 1971;Chambers 1987;Gopal 1987;Barko et al 1991;Heegaard et al 2001;Lougheed et al 2001;Mir 2009;Birk and Willby 2010;Alahuhta 2011;Uedeme-Naa et al 2011;Tamire and Mengistou 2012;Gecheva et al 2013; Sossey-Alaoui and Rosillon 2013). Riis et al (2000) while examining the relationship between environmental factors and aquatic plant composition in Danish streams found that alkalinity was the most important factor in predicting plant distribution.…”
Section: Water Quality and Sediment Related Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…had their greatest frequencies in older restorations, particularly in 2017. This variation and decline could be due to grazing from waterfowl (Lauridsen et al 1993), water level fluctuations (Chow-Fraser 2005), changes in light conditions (Bini et al 1999), temperature (Minc 1997, Smith andMoelyowati 1998), or changes in nutrient inputs (Lougheed et al 2001). …”
Section: Discussionmentioning
confidence: 99%
“…The distribution of macrophytes is often related to water chemistry, especially as influenced by eutrophication (e.g., Lehmann & Lachavanne, 1999). The significance of parameters such as morphometry, water levels, perturbations and disturbances, composition of bottom substrates, land-use in the catchment and surroundings, connectivity between water bodies, as well as interactions with the fish fauna has also been demonstrated (e.g., Jupp & Spence, 1977;Rørslett, 1991;Wright et al, 1992;Bornette & Amoros, 1996;Lehmann et al, 1997;Lougheed et al, 2001;Oertli et al, 2002). Many of these studies are concerned with the relationships between species richness of aquatic macrophytes and environmental variables but few involve study of a high number of individual species (e.g., Heegaard et al, 2001;Bio et al, 2002).…”
Section: Introductionmentioning
confidence: 99%